2019
DOI: 10.19044/esj.2019.v15n7p35
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Profitability in Banking Sector: An Evidence from Pakistan

Abstract: This research explores the association of bank specific characteristics and its profitability. Profitability of bank relates to external and internal factors i.e. size, capital, loan and deposit generally. The study is mainly concerned with the internal factors which have an effect on the profitability of the banks in Pakistan. 34 Banks including 21 Local Private Banks, 9 Public Sector Commercial Banks, 4 Foreign Banks and 4 Specialized Banks operate their services in Pakistan. Data has been taken of overall b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…It will impact the company's ability to generate profits in the next period to decrease and make its profitability as measured by a smaller ratio than in the previous period because the volume of credit extended is smaller than the previous period. This result contradicts Mahardian (2008) and Widianata (2012), Raza et al (2019), Duraj &Moci (2015), andAl Zaidanin (2020); this shows that the NOM ratio has a significant positive effect (ROA) on finances. Performance due to differences in data and the state of the financial ratios of the object under study.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…It will impact the company's ability to generate profits in the next period to decrease and make its profitability as measured by a smaller ratio than in the previous period because the volume of credit extended is smaller than the previous period. This result contradicts Mahardian (2008) and Widianata (2012), Raza et al (2019), Duraj &Moci (2015), andAl Zaidanin (2020); this shows that the NOM ratio has a significant positive effect (ROA) on finances. Performance due to differences in data and the state of the financial ratios of the object under study.…”
Section: Discussionmentioning
confidence: 72%
“…The standard NOM ratio set by Bank Indonesia is 6% or higher. Based on the empirical results of Mahardian (2008) and Widianata (2012), Raza et al (2019), Duraj & Moci (2015), and Al Zaidanin (2020), this shows that the NOM ratio has a significant positive effect (ROA) on financial performance. The following assumptions: H4: Net Operating Margin (NOM) positively impacts Islamic Commercial Banks' performance (ROA).…”
Section: The Effect Of Nom On the Performance (Roa) Of Islamic Commercial Banksmentioning
confidence: 96%
“…The study result aligns with the results of Mwangi et al (2018) and Al-Homaidi et al (2018), who found a positive relationship between total assets and financial performance. On the contrary, Raza et al (2019) found a negative relationship between total assets and financial performance.…”
Section: The Relationship Between Bank Size and Financial Performancementioning
confidence: 83%
“…Similarly, Raza et al (2019) examined the relationship between bank specific attributes (asset size, customers' deposit, loan to customers, capital adequacy) and the profitability of banks. The results from the analysis of data indicate that asset size had an inverse relationship with profitability, while customers' deposit does not have any significant influence on profitability of banks in Pakistan.…”
Section: Bank Size and Financial Performancementioning
confidence: 99%
“…The findings of the study using the data of 135 countries from 1995 to 2014 by Aizenman, Cheung & Ito, April (2017) [23] showed that the real interest rate affects private saving negatively whenever output volatility, old-age dependency, or financial development is over a specific limit and these effects are critical for the economy dependent upon a country's particular economic conditions. Raza, Hena & Saeed, (2017) [24] found the positive relationship between interest rate and bank deposit while negative relationship between savings and interest rate of scheduled banks listed in the State Bank of Pakistan during the period of 2002 to 2016. The study by Aslam, (2018) [25] revealed that the interest rate had influence on the savings for both long -run and short -run in Sri Lanka for the period of 1977 to 2017 and recommended to consider interest rate friendly policy for enhancing the savings in Sri Lanka by the policy makers.…”
Section: Interest Rate and Inflation On Savingsmentioning
confidence: 99%